ESL (ELL) literacy instruction [ a guidebook to theory and practice - Gunderson, Lee , 1942- (Routledge, 2009)
"This comprehensive research-based text provides both ESL and mainstream teachers with the background and expertise necessary to plan and implement reading programs that match the particular needs and abilities of their students." "As the number of ESL students in public schools continues to grow, so grows the need for teachers to have the background and skills necessary to provide these students with the best possible programs. This book is dedicated to that task."--BOOK JACKET